2018
DOI: 10.1039/c8cc04057e
|View full text |Cite
|
Sign up to set email alerts
|

Human histone demethylase KDM6B can catalyse sequential oxidations

Abstract: Biochemical studies on the histone lysyl demethylase KDM6B reveal it is capable of catalysing reactions on multiple lysine analogues, forming de-alkylated, hydroxylated, and oxidised products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
(20 reference statements)
0
4
0
Order By: Relevance
“…However, JHDMs were shown to be unable to de-alkylate substrates containing N ɛ -formyl-, N ɛ -acetyl-, or N ɛ -crotonyl [ 115 ]. In a separate study, the histone demethylase KDM6B was evaluated with a set of histone peptides bearing several unnatural analogues [ 116 ]. It was shown that KDM6B can efficiently demethylate N ɛ -diethyllysine, N ɛ -monomethylmonoethyllysine, and N ɛ -isopropyllysine.…”
Section: Erasing Kme3mentioning
confidence: 99%
“…However, JHDMs were shown to be unable to de-alkylate substrates containing N ɛ -formyl-, N ɛ -acetyl-, or N ɛ -crotonyl [ 115 ]. In a separate study, the histone demethylase KDM6B was evaluated with a set of histone peptides bearing several unnatural analogues [ 116 ]. It was shown that KDM6B can efficiently demethylate N ɛ -diethyllysine, N ɛ -monomethylmonoethyllysine, and N ɛ -isopropyllysine.…”
Section: Erasing Kme3mentioning
confidence: 99%
“…Analogous probes may also be useful for other Fe(II)/α-KG-dependent enzymes such as histone demethylases, which have been recently shown to accept N ε -alkylated-Lys analogs. 22 Transfecting probe-containing oligonucleotides or feeding nucleoside analogs for genomic incorporation 23 could offer a powerful means to localize TET enzymes or otherwise track epigenome dynamics in future work.…”
mentioning
confidence: 99%
“…Also, eyC, due to its cross-linking reactivity, can be applied to understand when and where TET isozymes are active in given cellular niches or to identify TET-like enzymes in other species, such as the TET-like enzyme from the amoeba Naegleria gruberi, which readily reacts with the probe (Figure S12). Analogous probes may also be useful for other Fe­(II)/α-KG-dependent enzymes such as histone demethylases, which have been recently shown to accept N ε -alkylated-Lys analogs . Transfecting probe-containing oligonucleotides or feeding nucleoside analogs for genomic incorporation could offer a powerful means to localize TET enzymes or otherwise track epigenome dynamics in future work.…”
mentioning
confidence: 99%
“…In a follow-up study Schofield and co-workers surprisingly found that KDM6B accepted alkylated lysine, resulting in the formation of de-alkylated, hydroxylated or carboxylated products. 100 However, KDM catalysis required the presence of the charged N e -alkylamino group to take place. Moreover, H3K P 9me3, and not H3K P 9me2, was found to be a substrate for KDM4A/D/E JmjC demethylases, indicating that selectivity could be achieved.…”
Section: Lysine Demethylasesmentioning
confidence: 99%